Encapsulation of Nicardipine Hydrochloride and Release from Biodegradable Poly(D,L-lactic-co-glycolic acid) Microparticles by Double Emulsion Process: Effect of Emulsion Stability and Different Parameters on Drug Entrapment - Soomherun, Nopparuj; Kreua-ongarjnukool, Narumol; Chumnanvej, Sorayouth; Thumsing, Saowapa (International Journal of Biomaterials, 2017)
Poly(D,L-lactic-co-glycolic acid) (PLGA) is an important material used in drug delivery when controlled release is required. The purpose of this research is to design and characterize PLGA microparticles (PLGA MPs) implants for the controlled release of nicardipine hydrochloride (NCH) in vitro. This study used the water-in-oil-in-water (w1/o/w2) double emulsion and solvent diffusion/evaporation approach to prepare PLGA MPs. Optimal processing conditions were found, such as polymer content, surfactant type, stabilizer concentration, inner and outer aqueous phase volumes, and stirring speed. The PLGA MPs for use as nicardipine hydrochloride (NCH) loading and release had spherical morphology, and the average diameter was smaller than 5.20±0.25 μm. The release kinetics were modeled to elucidate the possible mechanism of drug release. In vitro release studies indicated that the NCH release rate is slow and continuous. PLGA MPs are an interesting alternative drug delivery system, especially for use with NCH for biomedical applications.